Arbeitsrecht / Europäische Vorgaben der Unternehmensansiedlung - Krimphove, Dieter

Nikolaus Lenau: Savonarola. Ein Gedicht; Die Albigenser. Freie Dichtungen - Eke, Norbert Otto (Reclams Romanlexikon. Bd. 2: Von der Romantik bis zum Naturalismus)

Richard Beer-Hofmann: Der Tod Georgs - Eke, Norbert Otto (Reclams Romanlexikon. Bd. 3: 20. Jahrhundert I)

Die Wörlitzer Anlagen zwischen Englischem Landschaftsgarten und Bon-Sauvage-Utopie? - Seng, Eva- Maria (Von der Geometrie zur Naturalisierung. Utopisches Denken im 18. Jahrhundert zwischen literarischer Fiktion und frühneuzeitlicher Gartenkunst. Hallesche Beiträge zur Europäischen Aufklärung Bd. 10)

Gabriele von Glasenapp: Aus der Judengasse. Zur Entstehung und Ausprägung deutschsprachiger Ghettoliteratur im 19. Jahrhundert. Tübingen: Max Niemeyer Verlag, 1996 - Eke, Norbert Otto (Juden und jüdische Kultur im Vormärz. Hg. von Horst Denkler, Norbert Otto Eke, Hartmut Steinecke und Detlev Kopp (Forum Vormärz Forschung. Jahrbuch 1998))

Das große "Straßenei" - Wo einst die Stadtmauer stand - Büker, Petra (Paderborn - vom Werden und Wachsen unserer Stadt (Materialien, Unterrichtsentwürfe, Arbeitsmittel), Paderborner Geographische Studien, Bd. 3)

The Paderborn university BSP (PUB) library-design, implementation and performance - Bonorden, Olaf; Juurlink, Bernhardus; Von Otte, I.; Rieping, Ingo (Proceedings 13th International Parallel Processing Symposium and 10th Symposium on Parallel and Distributed Processing)
The Paderborn University BSP (PUB) library is a parallel C library based on the BSP model. The basic library supports buffered and unbuffered asynchronous communication between any pair of processors, and a mechanism for synchronizing the processors in a barrier style. In ad-dition, it provides routines for collective communication on arbitrary subsets of processors, partition operations, and a zero-cost synchronization mechanism. Furthermore, some techniques used in its implementation deviate significantly from the techniques used in other BSP libraries.

Resolution remains hard under equivalence - Kleine Büning, Hans; Lettmann, Theodor (Discrete Applied Mathematics)

Europaoffenes Lernen mit Grundschulkindern oder: Europa beginnt in der Primarstufe. Arbeitsgruppe im Rahmen des Symposiums: „Bildungsprojekt ‚Europa’ in der universitären Lehrerausbildung. Standortvergewisserung. Perspektivenentwicklung. Erfahrungspräsentation“. Universität Münster - Büker, Petra
Mai 1999

Resource Management for High-Performance PC Clusters - Brune, Matthias; Keller, Axel; Reinefeld, Alexander (Proc. Int. Conf. on High-Performance Computing and Networking (HPCN))
With the recent availability of cost-effective network cards for the PCI bus, researchers have been tempted to build up large compute clusters with standard PCs. Many of them are operated with workstation cluster management software in high-throughput or single user mode. For very large clusters with more than 100 PEs, however, it becomes necessary to implement a full fledged resource management software that allows to partition the system for multi-user access. In this paper, we present our Computing Center Software (CCS), which was originally designed for managing massively parallel high-performance computers, and now adapted to modern workstation clusters. It provides - partitioning of exclusive and non-exclusive resources, - hardware-independent scheduling of interactive and batch jobs, - open, extensible interfaces to other resource management systems, - a high degree of reliability.